Bacillus tequilensis PKDN31 and Bacillus licheniformis PKDL10 –As double headed swords to combat Fusarium oxysporum f. sp. lycopersici induced tomato wilt. (November 2022) - Karthika, S.; Remya, M.; Varghese, Sherin; Dhanraj, N.D.; Sali, Sangeeta; Rebello, Sharrel; Jose, Sebastian Midhun; Jisha, M.S.
Abstract: Wilt disease, caused by Fusarium oxysporum. f. sp. lycopersici, is a global threat to tomato production that needs to be addressed seriously. The current research envisages the use of two self-compatible Bacillus strains, Bacillus tequilensis PKDN31 and Bacillus licheniformis PKDL10, in a combinatorial approach. The spent supernatant of liquid cultures from strains PKDN31 and PKDL10 showed in vitro antifungal activity against Fusarium sp. attaining an inhibition percentage of 95.33% and 96.54%, respectively. The bacterial isolates lytic activity against Fusarium oxysporum was evaluated by scanning electron microscopic analysis and lytic enzyme production of amylase, lipase, protease and β-1, 3 glucanase. Furthermore, PKDN31 and PKDL10 produced siderophores and had root colonizing ability that enhanced the biocontrol efficiency. Combined in vivo inoculation of Bacillus tequilensis PKDN31 and Bacillus licheniformis PKDL10 on tomato seeds revealed that the strains could induce systemic resistance in tomato against Fusarium oxysporum. f. sp. lycopersici by increasing defence enzymes such as β-1, 3 glucanase, polyphenol oxidase, peroxidase, phenylalanine ammonia-lyase, chitinase, and total phenol accumulations. Pot culture experiments also proved the biocontrol efficacy of the above dual culture supplementation as this treatment displayed a better growth as well as defense against Fusarium challenge compared to the controls. The obtained results suggest that rhizobacterial isolates could be employed as systemic resistance inducers and biocontrol agents in tomato plants to protect against Fusarium wilt disease. Highlights: Two antagonistic Bacillus strains, Bacillus tequilensis PKDN31 and Bacillus licheniformis PKDL10 effectively inhibited Fusarium oxysporum. f. sp. lycopersici. The strains produced lytic enzymes viz. amylase, lipase, protease and β-1, 3 glucanase. The organisms were siderophore producers and had root colonising ability that enhanced the biocontrol efficiency. Biocontrol potential of the selected isolates was proved in vivo followed by elevated defence enzymes such as β-1, 3 glucanase, polyphenol oxidase, peroxidase, Phenylalanine ammonia-lyase, chitinase and total phenol accumulations in ISR experiment confirmed the activity. The study revealed that potential rhizobacterial isolates can be used as systemic resistance inducer in tomato plants and safeguard against Fusarium wilt disease.